2020
DOI: 10.1088/1755-1315/425/1/012043
|View full text |Cite
|
Sign up to set email alerts
|

Increase in egg production, egg quality and immunity of local chicken resulted by cross-breeding

Abstract: A series of study aimed to improve egg production, egg quality and immunity resulted by cross-breeding with Arab chickens and laying chickens has been observed on 400 chickens of 5-month old of hens was used and treatment was divided into 2 groups: medium and heavy type hens. Randomized Block Design was used and hens were fed on a laying diet contained 18% of crude protein content and 2900 kcal/kg of metabolism energy. Parameters observed were the number of daily eggs (hen/day), clutch, egg weight, egg shape, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
2
1
Order By: Relevance
“…The average HDP of Lurik, Wareng, Lokal Putih, and Ranupane chickens at the age of 7 to12 months (along six months of chicken raised) was 45.80%; 34.36%; 36.39%, and 35.87%, respectively (Table 3). This value was lower than Sartika et al (2011) study based on the Mx gene of native chicken (60-64%) and Yaman et al (2020) on crossbred Indonesian native chicken by average 47.80%. However, it was higher than Aseel chicken of Indian native chicken (36.23%) at 70 weeks (Haunshi et al 2011).…”
Section: Hen Day Production (Hdp) Of Local Chickencontrasting
confidence: 60%
“…The average HDP of Lurik, Wareng, Lokal Putih, and Ranupane chickens at the age of 7 to12 months (along six months of chicken raised) was 45.80%; 34.36%; 36.39%, and 35.87%, respectively (Table 3). This value was lower than Sartika et al (2011) study based on the Mx gene of native chicken (60-64%) and Yaman et al (2020) on crossbred Indonesian native chicken by average 47.80%. However, it was higher than Aseel chicken of Indian native chicken (36.23%) at 70 weeks (Haunshi et al 2011).…”
Section: Hen Day Production (Hdp) Of Local Chickencontrasting
confidence: 60%
“…As Sigolo et al, (2021) indicated, different plant extracts were delivered to broiler in drinking water and they had a significant impact on the feed intake of the animal. Body weight gain and egg production in T4 were not significantly different compared to control that could be the feed intake similarity between these treatments (Yaman et al, 2020).…”
Section: Feed Intake Egg Production and Egg Massmentioning
confidence: 80%
“…In addition, it can assist the farmers in constructing or expanding poultry farms. Research and development in the poultry sector can lead to innovations that can enhance egg production, such as new breeds with higher egglaying capacities (Yaman et al, 2020), improve feed formulations and develop disease prevention and control strategies (Akintunde et al, 2015).…”
Section: Resultsmentioning
confidence: 99%